Mortality rates in Poland in the years 1995-2006 - Mlekodaj, Stanisław; Krasucki, Piotr (Polish Journal of Public Health, 2010)
The most credible indicator of the health of the population and the efficiency of medical care are mortality rates in various age groups. Since death is the inevitable consequence of being born, the system efficiency is best measured by the shift of mortality towards older age bands. While analyzing the age structure of mortality in Poland in the years 1995-2006, the authors noticed its apparent shift towards the top age bands, especially in cardiovascular diseases (mostly infarct). This seems to be related to the endorsement of an effective cardiac prevention program in the years 1975-1995. Some progress, although not so impressive, has also been made as regards two other most dangerous “killers”: cancer and injuries.